Optimalisasi Pembelajaran Bahasa Arab di Madrasah Raudatul Amal Desa Margasari melalui Penyediaan Buku Saku Interaktif - Intan Bunga Aurel; Yuwan Fijar Anugrah; Tb. Abdul Hamid (Universitas 45 Surabaya, 2025)
This study aims to enhance Arabic language learning at Madrasah Raudatul Amal Desa Margasari by providing an interactive pocketbook as a more engaging and effective learning tool. One of the main challenges faced by the madrasah is the limited learning resources available to help students understand Arabic vocabulary and grammar. Therefore, the interactive pocketbook was designed to present the material in a structured manner, complemented by illustrations that facilitate students' understanding. The research employs the Participant Action Research (PAR) method, which involves the active participation of both teachers and students in every stage of the development and implementation of the pocketbook. The results indicate that the use of the interactive pocketbook can improve students' understanding of Arabic material and motivate them to be more active in their learning. Additionally, teachers feel supported in the teaching process. Although there were some challenges in distributing the books, the development of a digital version is expected to expand access to the material. This program is anticipated to make a significant contribution to enhancing Arabic language learning at Madrasah Raudatul Amal, both in Desa Margasari and in other madrasah facing similar challenges.